Asymptomatic canine vector-borne diseases and diagnostic performance: Comparison between blood smears vs. conventional PCR (Journal of Tropical Resources and Sustainable Science (JTRSS), 2024)
Across the globe, vector-borne diseases (VBD) are causes of health and economic concern, particularly for companion animals such as dogs and cats. The common clinical presentation ranges from subclinical to acute infection even a proportion with symptomatic manifestation. The diagnosis of asymptomatic animals with VBDs is quite challenging since veterinary practitioners do rely on presenting clinical signs to inform the choice of diagnostic plan. In Malaysia, blood smears (thin and thick) are employed in the diagnosis of VBDs such as babesiosis, anaplasmosis, theileriosis and trypanosomiasis. This method is readily available and inexpensive; however, the sensitivity and specificity are low as the diagnosis is strongly dependent on the experience of the examiner. Conventional polymerase chain reaction (PCR) on the other hand is used in larger veterinary clinics and hospitals in Malaysia and is only utilised when there is a suspicion of VBDs. This study attempts to compare the thin blood smear method and conventional PCR in the diagnosis of of Anaplasma phagocytophilum, A. platys, Babesia canis, B. gibsoni, Ehrlichia canis in dogs in Malaysia. Thirty clinically healthy dogs (17 males and 13 females) averaging 2 years of age were randomly selected from clinic walk-ins to screen for VBDs with both blood smear and conventional PCR. In general, the conventional PCR was 2.5 times more sensitive and specific than the blood smear in the detection of VBDs including Babesia canis, Babesia gibsoni and Ehrlichia canis in the asymptomatic sampled dogs. The detection rate for blood smears was 20% (6/30) in comparison with 50% (15/30). Therefore, it is imperative to conduct screenings for VBDs in dogs, even when they present as asymptomatic, in order to avert the oversight of potential health emergencies. Conventional PCR emerges as the recommended methodology for screening asymptomatic dogs for VBDs.
Keywords: asymptomatic; dogs; diagnostic methods; haemoparasites; Malaysia